Threat of Entry and Organizational-Form Choice: The Case of Franchising in Retailing - Nishida, Mitsukuni; Yang, Nathan (Journal of Marketing Research, 2020)
Retail expansion is led by multistore firms, which often mix two organizational forms: franchised and company-owned outlets (“franchising decisions”). The authors examine whether strategic considerations in entry and expansion play a role in organizational-form decisions (e.g., franchising) in retailing. The authors utilize store count and revenues for franchised and company-owned outlets of nationwide convenience store chains in 47 geographical markets in Japan between 1984 and 2010. The empirical analyses show that strategic considerations in entry and expansion, ignored in the literature on franchising, appear to influence an organizational-form decision: firms rely more on company-owned outlets for expansion when the threat of entry from competitor firms in adjacent markets increases. The authors examine two interpretations: the convenience of quick deployment and a credible signal. Numerical analyses of a simple dynamic model of entry and franchising confirm that company-owned-outlet-based expansion arises under heightened entry threat. The simulation analysis highlights how franchising decisions in response to an elevated threat of entry may be beneficial (or harmful) for an incumbent firm, which yields key implications for firms, consumers, and policy makers.